Genetic diversity among tomato accessions based on agro-morphological traits - Hussain, Izhar; Aslam Khan, Sher; Ali, Sajid; Farid, Abid; Ali, Naushad; Ali, Sardar; Masaud, Shah; Hussain, Ijaz; Azeem, Kamran; Raza, Haneef (Penerbit Universiti Kebangsaan Malaysia, 2018)
It is of great importance to know about the genetic diversity, conservation and classification for further utilization of tomato germplasm resources. Therefore, 40 tomato accessions were evaluated on the basic of agro-morphological traits for genetic diversity in 2014. The experiment was conducted at Agricultural Research Farm, University of Haripur and farmer field in Swabi, Khyber Pakhtunkhwa, Pakistan. Principal component analysis showed that five out of 27 principal components with an eigenvalue above 1.0 were considered for 74.10% of the total variance. The major contributing traits in variations were days to flowering (DFL), days to fruiting (DFR), fruit size (FS), fruit weight plant-1 (FW), yield plot-1 (YPP), yield hectare-1 (YPH), leaf length (LL), predominant fruit shape (PDFS), fruit length (FL), fruit width (FWidth), clusters plant-1 (CPP), fruits plant‑1 (FPP) and plant height (PH). The scattered plot of the PC’s revealed that the accessions were scattered in all the quarters, which is also a representative that high level of genetic variability was present. FW and FL were positively correlated with YPH. However, the remaining yield components indirectly contributed YPH. Cluster analysis divided 40 accessions into four main clusters (I, II, III and IV), each of which having 12, 11, 07 and 10 accessions. The accessions in clusters I and II were statistically similar and performed better in terms of yield and yield related traits. Grouping into different clusters was associated with their agro-morphological differences. These results could be serving as a useful resource for further characterization, preservation and breeding programs.